Impact of Escherichia coli Infection During Pregnancy on Metabolic, Immunological, and Kidney Health in Postpartum Women - Dumooa F. Al-Hameedawi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Pregnancy represents a vulnerable physiological state where bacterial infections, including Escherichia coli, may pose risks to maternal health. Specific Background: While acute outcomes of E. coli infection during pregnancy are documented, its postpartum consequences on metabolic, immunological, and renal systems remain insufficiently explored. Knowledge Gap: Limited evidence exists regarding persistent alterations in metabolic profiles, immune responses, and kidney function following infection during pregnancy. Aims: This study evaluates metabolic, immunological, and renal health in postpartum women 40 days after delivery with prior E. coli infection compared to healthy controls. Results: Women with prior infection showed significantly higher fasting blood glucose, cholesterol, triglycerides, blood pressure, inflammatory markers (CRP, IL-6, IL-8), and thyroid autoantibodies, alongside reduced vitamin D and calcium levels. Renal indicators revealed elevated serum creatinine and blood urea nitrogen with decreased eGFR. Novelty: This study provides integrated evidence of concurrent metabolic dysregulation, immune activation, and renal impairment in postpartum women following E. coli infection during pregnancy. Implications: These findings highlight the need for postpartum monitoring of metabolic, immunological, and renal parameters to identify potential long-term maternal health complications. Highlights:• Elevated glucose, lipid profiles, and blood pressure observed in affected women• Increased inflammatory cytokines and thyroid autoantibodies indicate immune alterations• Reduced kidney filtration markers suggest persistent renal dysfunction Keywords: Escherichia Coli Infection, Pregnancy, Postpartum Health, Metabolic Dysfunction, Renal Function